The soul, magic and melancholia: a critique of the therapeutic - McCormack, Laura (2019)
By establishing that, to begin with, soul was a cosmic matter and therapy took the form of a theurgic-magical-theological approach, I establish the genealogical and conceptual landscape wherein I claim that modern therapy (delivered through psychoanalytical models) cannot work, as it essentially reduces the ontologically rich, cosmic category of soul to mind and ‘self’ and ignores the soul’s necessity to harmonise with the body, the cosmos and the transcendent. A summative vision of soul, substantiated by mood, forms part of what I appeal to in venturing that the allowance of a theurgic-magical dimension provides a preferable picture to the models provided by contemporary psycho-therapeutic disciplines. This vision restores lost aesthetic and ethical dimensions and fully contextualises the human being in a resonant realm of participation, taken seriously in its capacity to impact on psychic health.